2013
DOI: 10.5455/vetworld.2013.109-112
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal parasitic infections in organized cattle farms of Meghalaya

Abstract: Aim: To know the gastrointestinal parasitic infections in cattle of Meghalaya, India. Materials and Methods: A total of 676 faecal samples of cattle were collected for a period of two years from different organized cattle farms of Meghalaya for detection of gastrointestinal parasitic infections, using standard techniques. Results: Out of 676 faecal samples examined, 191 (28.25%) faecal samples were found positive for gastrointestinal parasitic infections. The eggs of Strongyle spp. were found predominant (65.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 0 publications
6
16
1
3
Order By: Relevance
“…Similar results with higher prevalence rates had been reported recently by several workers from different parts of India showing that strongyles were the most frequent helminths prevalent in cattle (Jyoti et al 2011;Laha et al 2013;Krishnamurthy and D'souza 2014). Higher prevalence of strongyles may be due to more conducive environment for the development of the pre-parasites stages in the hot and humid environmental conditions prevalent in this region (Singh et al 2012a).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results with higher prevalence rates had been reported recently by several workers from different parts of India showing that strongyles were the most frequent helminths prevalent in cattle (Jyoti et al 2011;Laha et al 2013;Krishnamurthy and D'souza 2014). Higher prevalence of strongyles may be due to more conducive environment for the development of the pre-parasites stages in the hot and humid environmental conditions prevalent in this region (Singh et al 2012a).…”
Section: Discussionsupporting
confidence: 78%
“…But in case of buffaloes, highest prevalence rate was documented in monsoon followed by winter and summer (35.71 and 24.32 %, respectively), the difference being non-significant (p [ 0.05). High moisture content along with temperature prevailed during rainy season favors the growth and development of larvae is the reason behind highest prevalence of GI parasitic infections during monsoon as also observed in earlier studies carried by various workers (Laha et al 2013;Chattopadhyay and Bandyopadhyay 2013). Devoid of optimum moisture and temperature for development of larvae in the pasture during hot and cold season, could be the reason of lower and lowest prevalence during summer and winter seasons, respectively.…”
Section: Discussionmentioning
confidence: 63%
“…In the present study, it was observed that Strongyle was the most prevalent helminths in cattle. Similar results with higher prevalence rates of Strongyle had been reported earlier by several workers from different parts of India (Jyoti et al, 2011;Singh et al, 2012;Laha et al, 2013). Hamid et al (2016) from Central Java also reported high prevalence of Strongylidae in cattle.…”
Section: Age-wise Prevalence Of Gi Parasitic Infections In Cattlesupporting
confidence: 79%
“…The adult animals generally suffer from sub-clinical form of disease and act as a source of infection to young and/or newly added stock. A variable prevalence rate of coccidiosis in adult dairy animals has been reported by several workers worldwide, including India (Muraleedharan 2005;Manya et al 2008;Yu et al 2011;Dong et al 2012;Gupta et al 2012;Laha et al 2013). Recent studies from Punjab state reported a prevalence rate of 3.77 % (Singh et al 2012a) and 0.95 % (Singh et al 2012b) from cattle and buffalo populations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of coccidiosis in cattle and buffaloes has been well reported from different parts of world (Yu et al 2011;Dong et al 2012) including India (Manya et al 2008;Laha et al 2013) but information regarding prevalence of coccidiosis in cattle and buffalo populations from Punjab state seems to be sporadic Jyoti et al 2011;Singh et al 2012a, b). Moreover, no attempt has been made to determine the species composition of coccidian infection in Punjab.…”
Section: Introductionmentioning
confidence: 99%